DESAIN KURIKULUM PROGRAM TAHFIDZUL QUR’AN BERBASIS KEARIFAN LOKAL - Hefniy Hefniy; Raudatul Jannah (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2019)
This paper discusses the Curriculum Design of the Local Wisdom-based Tahfidzul Qur’an Program. The purpose of this study was to determine the curriculum planning of the Tahfidzul Qur'an program at Ibnu Kathir Islamic Boarding School in Jember. Memorizing the Qur'an is one of the strategies in instilling educational goals in Indonesia. The soul that is awakened in the memory of the Qur'an will feel peaceful. And they are classified as good human beings. How better, if humans continue to study, understand, read and memorize them in order to practice them in everyday life. Therefore, the contents of the Qur'an are not in doubt in building human character. The Qur'an is a combination of tahfidz and the Qur'an. The Qur'an is the word of God revealed to the Prophet Muhammad, written in the Manuscripts, moved regularly according to history, as well as readings including worship as a guide in human life. " The Qur'an is the great and holy book that Allah sent to us to meet all our needs, both physical and spiritual. This research uses descriptive qualitative approach. Data collection techniques using observation, interviews, and documentation. The results of research on the curriculum of the Tahfidzul Qur’an Program are based on local wisdom. 1). Tahfidul Qu’ran program planning has 2 programs including: regular and takhassus programs. 2). The implementation of the curriculum for the tahfidzul Qur’an program at the Ibnu Katsir boarding school for girls in Jember consists of 3 stages including: daily implementation, monthly implementation, annual implementation. 3). The evaluation of the curriculum of the tahfidzul Qur’an program at Ibnu Katsir's Islamic boarding school in Jember has 4 stages including: daily evaluation, monthly evaluation, annual evaluation and evaluation of open or public testing